Atlas shrugged - Rand, Ayn (Signet, 1957)
This is the story of a man who said that he would stop the motor of the world, and did. Is he a destroyer or a liberator? Why does he have to fight his battle not against his enemies but against those who need him most? Why does he fight his hardest battle against the woman he loves? The answers to these questions become clear when the reason behind the baffling events that play havoc with the lives of the amazing men and women in this remarkable book is uncovered . Tremendous in scope, breathtaking in its suspense, "Atlas shrugged" is Ayn Rand's magnum opus, and a premier moral apologia for Capitalism